Youth leadership development through training transfer and mentoring - Rumeli, Muaza Shifa; Arshad, Mohd Mursyid; Ismail, Ismi Arif; Md Rami, Ahmad Aizuddin (Human Resource Management Academic Research Society, 2021)
Training and training transfer are issues in the field of human resource development. Training is a necessity for all employees including youth leaders. Training transfer is a way to indicate the actions of the participants after attending the training program. Youth leadership is an element critically needed in nation building agenda. The establishment of youth leadership will form the line of successors that will maneuver the socioeconomic landscape. The involvement of new youth leadership talent can be enhanced through wider exposure and professional training, including training transfer and mentoring. This article attempts to understand the definition of youth leaders, transfer training and explore the challenges and expectations of leadership in the context of youth development. The objective is also to explore youth leadership development through training transfer and mentoring.